Leveraging Online Learning and Certification Platforms for Technical Skill Development: A Strategy to Mitigate Unemployment - Syed Far, Abid Hossain; Radhita Rahmina, Anika; Samayla Tazin, Mridula; Md. Tanjid, Hossain; Nuzhat, Tanisha (INTI International University, 2024)
The key objective of this study is to discover the role of online learning and certification platforms for technical skill development as a strategy to mitigate unemployment. In the world of information technology, various online learning and certification systems have proven to be useful in filling in the skills gap. Using a literature review, this paper explores how these mediums have become a major cause of reducing the level of unemployment. This paper also discusses tools like Coursera, edX, Squarespace, and LinkedIn for technical skills development and therefore the employee’s marketability, thus increasing employment opportunities. These platforms enable people to gain some of the most sought-after skills in today’s market at a cheaper price and much faster than such traditional Universities. These platforms provide recognition certificates that enable unemployed individuals to gain more employment chances, especially in emerging industries such as cloud computing, Data Science, and IT. Employers and jobseekers will equally benefit from these platforms and this will help in producing and enhancing a skilled workforce that will lead to reduced employment rates in the society. Additionally, this paper analyzes skill-based learning and certifications to meet the shifting demands of the labor market and to offer valuable insights for policymakers, educational institutions, and employers who seek ways to reduce the level of unemployment.